From ‘Asabiyyah to Community Solidarity: Group Fanatism in Contemporary Indonesian Elections from the Perspective of Ibn Khaldun and Hadith - Ilham Mustafa; Firman Firman; Iqbal Yahya Utama; Muhamad Rezi (Program Studi Hukum Tata Negara, 2026)
This article discusses group fanaticism in the phenomenon of contemporary Indonesian elections using the concept of 'asabiyyah by Ibn Khaldun and a hadith about the prohibition of blind fanaticism as an analytical framework. The aim of this study is to explain that group fanaticism is not always negative, because to a certain extent it can serve as a social energy that builds cohesion, political participation, and legitimacy of power. However, fanaticism can also damage democracy if it turns into blind loyalty, identity exclusivism, the spread of hoaxes, hate speech, and horizontal conflicts. This research uses a qualitative-conceptual approach through literature review of Ibn Khaldun's thoughts on ‘asabiyyah, a hadith about the 'rayah ‘immiyyah,' an explanation of the hadith, and literature on contemporary Indonesian elections. The findings show that group fanaticism in elections emerges through identity politics, loyalty to figures, volunteer militancy, religious sentiment, and digital polarization. From Ibn Khaldun's perspective, these phenomena can be understood as forms of social solidarity capable of mobilizing masses and strengthening political positions. However, from the hadith perspective, solidarity must be controlled by the values of truth, justice, and public interest so that it does not turn into reprehensible 'asabiyyah. This article concludes that the key to democracy is not eliminating group fanaticism but managing it into inclusive, rational, and democratic citizen solidarity through political education, program-based campaigns, strengthening the General Elections Commission (KPU) and the Election Supervisory Agency (Bawaslu), digital literacy, volunteer codes of ethics, and inter-group dialogue.